(untitled) (Nigerian Journal of Technology, 2014)
A model for dewaterability of conditioned sludge was derived based on data generated after dewaterability experiments using six sand drying beds. In these experiments, Six beds were used, the first bed contain no conditioner and served as control experiment. Ferric Chloride was added to the remaining five beds in the neighborhood of 1%, 2%, 3%, 4%, and 5% respectively, corresponding to 30g, 60g, 90g, 120g, and 150g of FeCl3 Seepage (sg) was derived as a linear function of time. The coefficient of correlation obtained from the linear regression of seepage against time corresponding to 30g, 60g, 90g, 120g and 150g are 0.860, 0.844, 0.781, 0.722 and 0.535 respectively. Moisture content of sludge was 86.69% when no coagulant was added, it was 69.47%, 57.32%, 54.01%, 52.79% and 47.81% when 30g, 60g, 90g, 120g and 150g doses were used with a range of 38.88%. Dewaterability enhancement ratio was 1:1 for control experiment, 1:27.72, 1:46.59, 1:51.72, 1:53.62 and 1:61.34 for 30g, 60g, 90g, 120g, and 150g doses respectively. Statistical test parameter, “p-value” was computed for each coagulant dose and hypothesis tested at 95% level of significance. The “p-value” results corresponding to 30g, 60g, 90g, 120g and 150g are 0.000, 0.001, 0.003, 0.008 and 0.073. Based on the decision rule, it was concluded that the model is adequate. This model is good, but its deficiency lies in the fact that the coefficient of correlation between measured and calculated quantities of seepage at specified coagulant doses decrease with increase in coagulant dosage. Though, the higher the quantity of coagulant used, the higher the dewaterability of sewage sludge which is a big plus. The disadvantage of using coagulants in dewatering sludge lies in the fact that the effluent cannot be recycled for consumption because of the toxic Ferric Chloride that has been used as conditioner. It is recommended that further research be carried out to improve on this already existing model. http://dx.doi.org/10.4314/njt.v33i3.24